Tinjauan Normatif Tentang Tanggung Jawab Direksi Terhadap Karyawan yang Melakukan Perbuatan Melawan Hukum Memberikan Diskon Secara Sepihak Ditinjau Dari Doktrin Piercing The Corporate Veil dan Dihubungkan dengan Undang-Undang Nomor 40 Tahun 2007 Tentang P - Haetami, Vikri; Abas, Muhamad; Yuniar Rahmatiar; Lubis, Adyan (Universitas Ekasakti, 2024)
In Law No. 40 of 2007 concerning limited liability companies, the responsibilities of a director are regulated, but the directors of PT. Antam acted in bad faith in holding its employees accountable for their actions. This research uses normative juridical qualitative research methods. Based on the findings of the discussed research, it can be inferred that the implementation of Article 97, paragraph 3 of Law No. 40 of 2007 regarding Limited Liability Companies, which holds every director fully liable for company losses if proven guilty or negligent in fulfilling their duties as outlined in paragraph 2, is yet to be fully enforced. The decision of the Panel of Judges in this case does not take into account the doctrine of Piercing the Corporate Veil for directors to be responsible for the actions of their employees. As a result, employees who are under the responsibility of the directors are jointly and severally responsible with the Company's directors. The judge's considerations at the cassation level court imposed punishment not only on the PT. Antam, but rather the employees of PT. Antam was also given sanctions jointly and severally with PT. According to the author's analysis, Antam is not in accordance with the Piercing The Corporate Veil doctrine, where responsibility should be delegated entirely to the company's directors. Basically, the Piercing the Corporate Veil doctrine is a doctrine that imposes full responsibility on the company or company directors for certain things.